Perlindungan Hukum Terhadap Konsumen Yang Tidak Menerima Produk Pembelian Jasa Titip (Jastip) Berupa Tiket Konser Melalui Media Twitter Ditinjau Dari Hukum Positif Dan Hukum Islam - Cholqi Choirunnisa; Nisbati Sandiyah Humaeroh; Rahma Eka Fitriani (LPPM Universitas Sains dan Teknologi Komputer, 2023)
The Criminal Code (KUHP) regulates several forms of theft committed against property. The crime of fraud is defined in Articles 378 to 395 of Chapter XXV of the Penal Code, which further classifies different types of fraud into more nuanced categories. This type of theft, known as